Counterparty risk in material supply contracts - Nina Boyarchenko; Anna M. Costello (Federal Reserve Bank of New York, 2014)
This paper explores the sources of counterparty risk in material supply relationships. Using long-term supply contracts collected from SEC filings, we test whether three sources of counterparty risk - financial exposure, product quality risk, and redeployability risk - are priced in the equity returns of linked firms. Our results show that equity holders require compensation for exposure to all three sources of risk. Specifically, offering trade credit to counterparties and investing in relationship-specific assets increase the firm's exposure to counterparty risk. Further, we show that contracts with protective financial covenants and product warranties mitigate the transmission of risk. Overall, we provide evidence on the channels of supply-chain risk, and we show that shareholders recognize the role of contractual features in mitigating counterparty risk.
Keywords: G14; G19; L00; L14; 330; supply contracts; financial covenants; counterparty risk premia